Evaluation of Right and Left Ventricular Function in Ebstein Anomaly Using RVGLS and LVGLS: A Narrative Literature Review - Sembiring, Matthew Risdian Pratama; Lefi, Achmad; Kartikasari, Dian Paramita (Jurnal Ilmiah Kesehatan, 2025)
Ebstein anomaly is a rare congenital heart defect characterized by tricuspid valve malformation, atrialization of the RV, and hemodynamic disturbances that may affect both ventricles. Assessing ventricular function in this condition is essential because it is closely related to disease progression, clinical symptoms, and long term prognosis. Conventional parameters such as TAPSE, RVFAC, and LVEF are commonly used but have limitations. Speckle Tracking Echocardiography (STE), through Right Ventricular Global Longitudinal Strain (RVGLS) and Left Ventricular Global Longitudinal Strain (LVGLS), provides higher sensitivity for detecting ventricular dysfunction. This narrative literature review evaluates the role of RVGLS and LVGLS in patients with Ebstein anomaly. Evidence shows that RVGLS is more accurate in identifying RV dysfunction compared with TAPSE and RVFAC, and possesses strong prognostic value for mortality. LVGLS can detect LV dysfunction at a subclinical stage even when LVEF remains preserved, reflecting involvement of longitudinal myocardial fibers due to ventricular interdependence and secondary remodeling. After tricuspid valve surgery, both RVGLS and LVGLS remain sensitive indicators of changes in ventricular performance. Overall, RVGLS and LVGLS demonstrate superiority over conventional systolic parameters and are recommended as primary tools for evaluating biventricular function in patients with Ebstein anomaly